Allegiance to New Sports: Sports Marketing in Indian Perspective - Dham, Swati Oberoi; Mishra, Pratika (Indian Journal of Marketing, 2015)
Marketing of sports is very different from marketing through sports. While one takes care of marketing of sports-related goods, equipments, and merchandise, marketing through sports deals with promotion of any product through sports. Sports and events which form a part of the service industry today are sources of big money for the nation. In India, where cricket is a religion, and Sachin Tendulkar is God, it is important to understand how and why other new and upcoming sports such as F1 car racing, football, tennis, and so forth can be brought to the same marketable and fan following stage. This paper explored the concept of consumer behavior to understand why some sports are better followed than others.